Outcomes of adult medulloblastoma treated with a multimodality approach: A tertiary cancer center experience - Mallick, Supriya; Gandhi, Ajeet Kumar; Benson, Rony; Sharma, Daya Nand; Haresh, Kunhi Parambath; Gupta, Subhash; Julka, Pramod Kumar; Rath, Goura Kisor (South Asian Journal of Cancer, 2015)
Objectives: Adult medulloblastoma (AMB) is a rare central nervous system tumor. We aimed to analyze the treatment outcomes of AMB treated at our institute with surgery followed by craniospinal irradiation (CSI) and adjuvant chemotherapy. Methods: We retrospectively evaluated the treatment charts of 31 patients of AMB treated from 2003-2011. The patient demography, treatment details and survival data were collected in a predesigned proforma. Kaplan Meier method was used to analyze disease free survival (DFS) and the impact of prognostic factors was determined by univariate analysis (log rank test). Results: Male: Female ratio was 21:10. Cerebrospinal fluid dissemination was noted in 16% cases. CSI (36 Gray at 1.8 Gray/fraction to entire neuraxis and 20 Gray at 2 Gray/fraction boost to posterior fossa) was used in all cases. 26 patients received adjuvant chemotherapy (carboplatin plus etoposide). Median follows up was 26.85 months (9.47-119.73 months). The estimated 3 and 5 years DFS was found to be 84.9% and 50.7% respectively. On univariate analysis, tumor located laterally had a trend towards better DFS (HR 3.04; 95%CI 0.722 to 12.812; P = 0.07) compared to midline tumors. Other factors like adjuvant chemotherapy, age, gender, surgical extent had no statistically significant impact on survival. Conclusion: The results of our study (largest series from India) show that the regimen of surgery, adjuvant CSI and chemotherapy is feasible and confers descent survival. AMB patients should be treated with a multimodality approach in a tertiary care centre.
Keywords: Adult medulloblastoma; chemotherapy; radiation